Seleção de progênies de mini alface biofortificadas: características agronômicas e resistência à Pectobacterium carotovorum subsp. carotovorum - Jacinto, Ana Carolina Pires (2021)
Lettuce is the most consumed and most economically important leafy vegetable in the world. Allied to this, the Brazilian consumer is increasingly looking for differentiated products, such as the mini lettuce segment. However, production is hampered by numerous pathogens, with emphasis on Pectobacterium carotovorum subsp. carotovorum, which causes soft rot in lettuce. Thus, the objective of this work was to carry out the selection of biofortified mini lettuce genotypes, with good agronomic characteristics and resistance to Pectobacterium carotovorum subsp. carotovorum. The experiments were conducted in the field and in a greenhouse (UFU). The experimental design used in the biofortified mini lettuce genotype selection experiment, with good agronomic characteristics, was in randomized blocks, with 12 treatments (11 mini lettuce genotypes of the F5: 6 generation and the Purpurita mini lettuce cultivar) and four replications. When the plants showed maximum vegetative development, the following were evaluated: SPAD index, stem and plant diameter, stem length, plant height, number of leaves, fresh weight and resistance to tipping. For the resistance or susceptibility test, the experimental design used was completely randomized, with 13 treatments (11 genotypes of biofortified mini lettuce and the cultivars Vitória de Santo Antão - moderately resistant and Purpurita - susceptible) and three replications. The bacterial suspension was inoculated and evaluated: disease severity, evaluated 16 days after inoculation; area under the disease progress curve (AUDPC), calculated separately at 4, 8, 12 and 16 days after inoculation, as well as the sum of data from all days of assessment and disease resistance class. The genotypes UFU 215#1 and UFU 215#2 stood out for their high concentration of (SPAD). The genotypes UFU 66#4, UFU 215#1 and UFU 215#7 showed high resistance to blossoming. All genotypes were classified as resistant or moderately resistant to the UFU A7 isolate from P. carotovorum subsp. carotovorum. In this sense, the genotypes UFU 66#3, UFU 66#7 and UFU MC MINIBIOFORT2 stand out, as they have the three associated characteristics in the same genotype.